Pengembangan Kompetensi Profesionalisme Guru di Era Digital - Maya Veronica Sianturi; Marta Putri Uli Simanjuntak (Jurnal Pendidikan Agama dan Teologi, 2024)
This research aims to evaluate the development of teachers' professionalism in the digital era. The applied research method is a Literature Review. Data collection is conducted through library research to identify articles relevant to the research topic. The government strives to develop the teaching profession as a strong and respected occupation, as reflected in the enactment of Law No. 14 of 2005 concerning Teachers and Lecturers, which aims to develop the teaching profession through legal protection. With the rapid advancement of digital technology, teachers need to have appropriate qualifications to perform their duties effectively. A study indicates that strategies to enhance teacher competence involve comprehensive monitoring of learning aspects and gradual support from school principals and supervisors through training. The professionalism of teachers is reflected in their skills in applying information technology precisely and developing creative and innovative teaching methods.